KAKANG KAWAH DAN ADHI ARI-ARI: SAUDARA SPIRITUAL ORANG JAWA (TINJAUAN ANGELOLOGI KRISTIANI) - Chrisdinando, Gerardus; Tinambunan, Edison R.L. (Universitas Sanata Dharma, 2024)
Javanese people believe that babies are not born alone. Babies are born with two spiritual siblings: kakang kawah (the amniotic fluid) and adhi ari-ari (the placenta). These two figures accompany humans in early life and become guardians until the end of someone’s life. It seems that the concept of kakang kawah and adhi ari-ari is also found in the concept of the Christian faith, namely the Guardian Angel, who is believed to be God's messenger, a guardian for everyone. Christian Javanese people who want to preserve Javanese culture will undoubtedly find some difficulties applying tradition and faith, even though the two concepts are similar. This paper will discuss the concepts of kakang kawah and adhi ari-ari from a Christian angelology perspective. The aim is to discover how far the concepts and rituals of kakang kawah and adhi ari-ari in the Javanese tradition are acceptable in the Christian faith. The methodology used in this paper is a literature study, and the methods used here are descriptive and comparative studies. The results of this study are the findings of the relationship between the two concepts, namely that the concepts of kakang kawah and adhi ari-ari are similar and do not conflict with the concept of guardian angels in the Christian faith. Thus, the concepts of kakang kawah and adhi ari-ari can be used to inculturation the Indonesian Catholic Church. This research also attempts to systematize the concepts of kakang kawah and adhi ari-ari. In addition, this research will be very useful for the catechesis of faith to the Javanese within the framework of the inculturation of the Catholic Church in Nusantara.AbstrakOrang Jawa percaya bahwa bayi tidak lahir sendirian. Bayi lahir bersama dua saudara spiritualnya, yakni kakang kawah (air ketuban) dan adhi ari-ari (adik ari-ari). Dua sosok ini mendampingi kehidupan awal manusia dan kemudian menjadi penuntun kehidupan hingga akhir hayat. Rupanya konsep kakang kawah adhi ari-ari juga terdapat dalam konsep iman Kristiani, yakni Malaikat Pelindung, yang diyakini merupakan utusan Tuhan sebagai penuntun kehidupan bagi setiap orang. Orang Jawa yang ingin melestarikan budaya Jawa meski telah memeluk Kekristenan tentu akan menemukan beberapa kesulitan untuk menerapkan tradisi bersamaan dengan iman, meskipun dua konsep tersebut serupa. Tulisan ini akan membahas konsep kakang kawah dan adhi ari-ari dari perspektif angelologi Kristiani. Tujuannya adalah mengetahui sejauh mana konsep dan ritual-ritual kakang kawah dan adhi ari-ari dalam tradisi Jawa dapat diterima dalam iman Kristen. Pengumpulan data dilakukan dengan cara studi pustaka. Metodologi yang digunakan adalah deskriptif dan studi komparatif. Hasil dari penelitian ini adalah temuan relasi antara kedua konsep tersebut, yaitu bahwa konsep kakang kawah dan adhi ari-ari adalah serupa dan tidak bertentangan dengan konsep malaikat pelindung dalam iman Kristiani. Dengan demikian, konsep kakang kawah dan adhi ari-ari dapat digunakan sebagai sarana inkulturasi Gereja Katolik Indonesia. Penelitian ini berusaha membuat sistematisasi konsep kakang kawah dan adhi ari-ari. Selain itu, penelitian ini akan sangat berguna bagi katekese iman kepada orang Jawa dalam kerangka inkulturasi Gereja Katolik di Nusantara.